2009
DOI: 10.3899/jrheum.080734
|View full text |Cite|
|
Sign up to set email alerts
|

The Efficacy and Safety of Milnacipran for Treatment of Fibromyalgia. A Randomized, Double-blind, Placebo-controlled Trial

Abstract: Milnacipran is safe and effective for the treatment of multiple symptoms of FM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
267
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(287 citation statements)
references
References 52 publications
13
267
2
5
Order By: Relevance
“…These results differ from those in previous trials, in which treatment with a higher dosage of milnacipran 200 mg/day (100 mg twice daily) led to significant improvements in cognitive function after 3 and 6 months of treatment (6,7). More studies using structured cognitive testing in addition to self-report measures are needed to assess further the cognitive function of patients with fibromyalgia and the response of cognitive symptoms to treatment.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…These results differ from those in previous trials, in which treatment with a higher dosage of milnacipran 200 mg/day (100 mg twice daily) led to significant improvements in cognitive function after 3 and 6 months of treatment (6,7). More studies using structured cognitive testing in addition to self-report measures are needed to assess further the cognitive function of patients with fibromyalgia and the response of cognitive symptoms to treatment.…”
Section: Discussioncontrasting
confidence: 83%
“…The results of this trial are consistent with those of 2 previous pivotal studies of milnacipran using the same composite response criteria (6,7). Use of the composite responder definition in these studies allows for an assessment of clinically meaningful improvements across multiple symptom and function domains in individual patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These studies showed that Savella (100 and 200 mg/day) demonstrated clinically significant improvements compared with placebo in treating fibromyalgia. A larger number of Savella-treated patients experienced at least a 30% reduction in pain from baseline as well meeting the criteria for a treatment response as measured by improvements in pain, physical function, and patient global assessment (4,5).…”
mentioning
confidence: 99%